2020
DOI: 10.1103/physrevb.102.245136
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization-induced gapped and gapless states on the surface of magnetic topological insulators

Abstract: The layered MnBi2nTe3n+1 family represents the first intrinsic antiferromagnetic topological insulator (AFM TI, protected by a combination symmetry S ) ever discovered, providing an ideal platform to explore novel physics such as quantum anomalous Hall effect at elevated temperature and axion electrodynamics. Recent angle-resolved photoemission spectroscopy (ARPES) experiments on this family have revealed that all terminations exhibit (nearly) gapless topological surface states (TSSs) within the AFM state, vio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 104 publications
(115 reference statements)
9
41
0
Order By: Relevance
“…45 and 50, more states appear inside the surface hybridization gap, which can be interpreted as bulk states according to our theory. We also notice that most previous calculations based on slab models [18,43,47,51,53,54,56] found gapped surface states for the QL1 surface. These calculations adopted slab models with thicknesses from 5 to 13 nm.…”
Section: (D)-(f)supporting
confidence: 51%
See 2 more Smart Citations
“…45 and 50, more states appear inside the surface hybridization gap, which can be interpreted as bulk states according to our theory. We also notice that most previous calculations based on slab models [18,43,47,51,53,54,56] found gapped surface states for the QL1 surface. These calculations adopted slab models with thicknesses from 5 to 13 nm.…”
Section: (D)-(f)supporting
confidence: 51%
“…However, many ARPES experiments and calculations concluded that the QL1 surface is gapped [42,43,45,47,48,51,54] while some other works claimed the gapless feature for the same surface [35,45,46,49,52,53]. We note that the gapped nature of surface states is crucial to realizing QAHE, Chern insulator, or AI, which requires insulating thin films including their surfaces.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…5(c) and 5(d)). While the focus of this work is on the technical capabilities of MRPES, we note that the interpretations of various spectral features from MnBi 4 Te 7 are currently under debates 44,45,48 . Based on our previous studies 49,50 , we attribute the large electronlike pocket on the MBT termination to a pair of Rashbasplit states.…”
Section: B Mnbi 4 Tementioning
confidence: 99%
“…While MnBi 4 Te 7 (m=1) [12][13][14][15][16][17][18][19] and MnBi 6 Te 10 (m=2) [17][18][19][20][21] have been found to be AFM similar to MnBi 2 Te 4 (m=0), MnBi 8 Te 13 (m=3) clearly distinguishes from other compounds with a unique FM interaction between neighboring MnBi 2 Te 4 layers and QAHE at zero field has been predicted at low temperature, 22,23 highlighting the importance of interlayer interaction.…”
mentioning
confidence: 90%